2007
DOI: 10.1152/ajpregu.00029.2007
|View full text |Cite
|
Sign up to set email alerts
|

Transport of a fluorescent cAMP analog in teleost proximal tubules

Abstract: Previous studies have shown that killifish (Fundulus heteroclitus) renal proximal tubules express a luminal membrane transporter that is functionally and immunologically analogous to the mammalian multidrug resistance-associated protein isoform 2 (Mrp2, ABCC2). Here we used confocal microscopy to investigate in killifish tubules the transport of a fluorescent cAMP analog (fluo-cAMP), a putative substrate for Mrp2 and Mrp4 (ABCC4). Steady-state luminal accumulation of fluo-cAMP was concentrative, specific, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 35 publications
5
21
0
Order By: Relevance
“…To investigate whether aspirin is a substrate and can be transported by MRP4, we used DGP, obtained from HV human platelets, because MRP4 is predominantly Aspirin and MRP4 in Platelets localized in dense granule membranes (12). To demonstrate that aspirin is a substrate for MRP4, we used Fluo-cAMP, a fluorimetric analog of cAMP (17). In DGP both aspirin and SA reduced the intake of Fluo-cAMP, suggesting that both aspirin and SA interact with MRP4 solely and specifically (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate whether aspirin is a substrate and can be transported by MRP4, we used DGP, obtained from HV human platelets, because MRP4 is predominantly Aspirin and MRP4 in Platelets localized in dense granule membranes (12). To demonstrate that aspirin is a substrate for MRP4, we used Fluo-cAMP, a fluorimetric analog of cAMP (17). In DGP both aspirin and SA reduced the intake of Fluo-cAMP, suggesting that both aspirin and SA interact with MRP4 solely and specifically (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Fluo-cyclic adenosine monophosphate MRP4-mediated transport. The MRP4-dependent 8-Fluocyclic adenosine monophosphate (cAMP) uptake in platelet granules was analyzed as previously described (17). Briefly DGP was incubated with 8-Fluo-cAMP, aspirin, and SA (all 20 mol/l).…”
Section: Sources Of Materialsmentioning
confidence: 99%
“…Fluo-cAMP was used to study ABCC4 functionality as this substance was shown to be a substrate for human ABCC4 (24). Again, PSC 833 and MK 571 were used as inhibitors in the experiment.…”
Section: Functional Analysis Of Cells Grown In 96 Well Microplatesmentioning
confidence: 99%
“…Substrates of ABCC1 include fluorescein methotrexate (22) and sulforhodamine 101 (23), substrates of ABCC4 are cyclic nucleotides cAMP and cGMP, adefovir and topotecan (19). Moreover, fluo-cAMP (a fluorescein-linked cAMP analogue) transport is mediated by this transporter (24). Both, ABCC1 and ABCC4 can be inhibited with MK 571.…”
Section: Introductionmentioning
confidence: 99%
“…One reason for this is that in marine teleost proximal tubules the tubular lumen remains patent and all the steps in the excretory transport of fluorescent substrates can be visualized for several hours in the living tubules. Indeed, studies with teleost renal tubules have identified fluorescent substrates for specific ABC transporters, e.g., P-glycoprotein and Mrp4 (Abcc4), that have translated to mammalian systems (Schramm et al, 1995;Miller et al, 2000;Reichel et al, 2007Reichel et al, , 2010. Moreover, with regard to P-glycoprotein, there are clear molecular-level similarities between the killifish and human transporters.…”
Section: Sphingolipid Signaling In Renal Proximal Tubulementioning
confidence: 99%